Molecular simulations reveal intricate coupling between agonist-bound β-adrenergic receptors and G protein - Yanxiao Han; John R.D. Dawson; Kevin R. DeMarco; Kyle C. Rouen; Khoa Ngo; Slava Bekker; Vladimir Yarov-Yarovoy; Colleen E. Clancy; Yang K. Xiang; Surl-Hee Ahn; Igor Vorobyov (iScience)
Summary: G protein-coupled receptors (GPCRs) and G proteins transmit signals from hormones and neurotransmitters across cell membranes, initiating downstream signaling and modulating cellular behavior. Using advanced computer modeling and simulation, we identified atomistic-level structural, dynamic, and energetic mechanisms of norepinephrine (NE) and stimulatory G protein (Gs) interactions with β-adrenergic receptors (βARs), crucial GPCRs for heart function regulation and major drug targets. Our analysis revealed distinct binding behaviors of NE within β1AR and β2AR despite identical orthosteric binding pockets. β2AR had an additional binding site, explaining variations in NE binding affinities. Simulations showed significant differences in NE dissociation pathways and receptor interactions with the Gs. β1AR binds Gs more strongly, while β2AR induces greater conformational changes in the α subunit of Gs. Furthermore, GTP and GDP binding to Gs may disrupt coupling between NE and βAR, as well as between βAR and Gs. These findings may aid in designing precise βAR-targeted drugs.